Model komunikasi Ideal antara Tuna Netra dan Visual Reader dalam Menonton Film - Cut Meutia Karolina; Eni Maryani; Dian Wardiana Sjuchro (Jurnal Komunikasi, 2019)
Bioskop Harewos as a special cinema for the audiences with visual impairments have a uniqueness.  The uniqueness that replaces the role of Audio Description with individuals, known as Visual Reader. The Visual Reader is in charge of telling the visual scene of the movie being watched. The purpose of this research is to find out the obstacles experienced of the audiences with visual impairments when watching movies accompanied by the Visual Reader; knowing the barriers of Visual Reader in giving the visual description of the movie to the audiences with visual impairments; and learned about the Bioskop Harewos preparations for the Visual Reader and the audiences with visual impairments before the watching process took place.   Research methods using qualitative case studies. The results of the research found that spectators of the audiences with visual impairments experienced have several obstacles when communicating with the Visual Reader in the process of watching movies at the Bioskop Harewos. The obstacles were assessed from various aspects, therefore visual message from the film was not obtained to the maximum. Visual Reader also has difficulties in narrating visual messages to the audiences with visual impairments.  Keywords : film, Audiences, Visual Impairments, Visual Reader, Cinema